Body movements during the off-ice execution of back spins in figure skating - Mapelli, A.; Rodano, R.; Fiorentini, A.; Giustolisi, A.; Sidequersky, F. V.; Sforza, C. (Journal of Electromyography and Kinesiology, 2013)
Using an optoelectronic motion capture system, we quantitatively assessed the arrangement of body segments and the displacement of the horizontal projection of the center of mass (CM) in seven skaters performing off-ice back spins on a rotating device (spinner). The position of the CM at the beginning of the spins was not a determining factor, but its rapid stabilization towards the center of the spinner, together with the achievement of a stable arrangement of trunk and limbs, was crucial to get the dynamic equilibrium, necessary for a lasting performance. At full spinning, however, there was an indicative variety of individual body postures. A final deceleration, associable with the loss of body equilibrium, was detected in the last spin of most of skaters.